High Level Aminoglycoside Resistance and Distribution of Aminoglycoside Resistant Genes among Clinical Isolates of Enterococcus Species in Chennai, India - Elango Padmasini; R. Padmaraj; S. Srivani Ramesh (The Scientific World Journal)
Enterococci are nosocomial pathogen with multiple-drug resistance by intrinsic and extrinsic mechanisms. Aminoglycosides along with cell wall inhibitors are given clinically for treating enterococcal infections. 178 enterococcal isolates were analyzed in this study. E. faecalis is identified to be the predominant Enterococcus species, along with E. faecium, E. avium, E. hirae, E. durans, E. dispar and E. gallinarum. High level aminoglycoside resistance (HLAR) by MIC for gentamicin (GM), streptomycin (SM) and both (GM + SM) antibiotics was found to be 42.7%, 29.8%, and 21.9%, respectively. Detection of aminoglycoside modifying enzyme encoding genes (AME) in enterococci was identified by multiplex PCR for aac(6′)-Ie-aph(2′′)-Ia; aph(2′′)-Ib; aph(2′′)-Ic; aph(2′′)-Id and aph(3′)-IIIa genes. 38.2% isolates carried aac(6′)-Ie-aph(2′′)-Ia gene and 40.4% isolates carried aph(3′)-IIIa gene. aph(2′′)-Ib; aph(2′′)-Ic; aph(2′′)-Id were not detected among our study isolates. aac(6′)-Ie-aph(2′′)-Ia and aph(3′)-IIIa genes were also observed in HLAR E. durans, E. avium, E. hirae, and E. gallinarum isolates. This indicates that high level aminoglycoside resistance genes are widely disseminated among isolates of enterococci from Chennai.